Deep Knowledge : Ways of Knowing in Sufism and Ifa, Two West African Intellectual Traditions - Ogunnaike, Oludamini (Africana religions., 2020)
"Studies the epistemologies of two of the most influential intellectual/spiritual traditions of West Africa: Tijani Sufism and Ifa"--